Wilsonian Visions : The Williamstown Institute of Politics and American Internationalism after the First World War - McAllister, James, 1964- (Book collections on Project MUSE., 2021)
"This book delivers an account of the liberal internationalism of Harry Garfield and the Williamstown Institute of Politics"--